The territorial state in the perceptions of the Egyptian elite in the early twentieth century - BRAI, FATH (Journal of Social Sciences and Humanities, 2021)
The interaction of a number of factors in Egypt, such as the Napoleon Bonaparte Campaign (1798-1801), the open policy of the West pursued by Muhammad Ali basha (1805- 1848), and then the British campaign in 1882, led to the production of a number of new ideas that characterized the Egyptian intellectual arena and The most important of these is the emergence of the Qotari regional trend that prevailed at the beginning of the year 1900. It works according to a pure Egyptian nationalism, considering Egypt as a distinct civilized entity that cannot be confined to a purely Arab, Islamic, Pharaonic or Ottoman orientation. However, it has a special entity according to a Qotari geographic principle based on the Nile River as a natural determinant, hence this paper seeks to reveal the Egyptian primacy in identifying the principle of Qotari, and then embrace the Qotari national orientation after the presentation of the most important national intellectual currents prevailing Egypt in the early twentieth century AD, He also presented the most important representations and propositions of the Qotari national orientation among the elite of Egypt in that period and try to find out the position of supporters of this trend of the trend of Arab nationalism in Egypt.